Dairy intensification: Drivers, impacts and alternatives - Clay, N; Garnett, T; Lorimer, J (Springer, 2019)
Dairy production systems have rapidly intensified over the past several decades. Dairy farms in many world regions are larger and concentrated in fewer hands. Higher productivity can increase overall economic gains but also incurs site-specific social and environmental costs. In this paper, we review the drivers and impacts of dairy intensification. We identify in the literature four prominent concerns about dairy intensification: the environment, animal welfare, socioeconomic well-being, and human health. We then critically assess three frameworks-sustainable intensification, multifunctionality, and agroecology-which promise win-win solutions to these concerns. We call for research and policy approaches that can better account for synergies and trade-offs among the multiple dimensions of dairy impacts. Specifically, we suggest the need to (1) consider dairy system transitions within broader processes of social-environmental change and (2) investigate how certain framings and metrics may lead to uneven social-environmental outcomes. Such work can help visualize transformations towards more equitable, ethical, and sustainable food systems.